The Effect of Work Discipline, Work Environment and Work Motivation on Employee Performance - Maulidiah, Uzla; Baskoro, Heru (Majapahit Journal of Islamic Finance and Management, 2025)
This research aimed to investigate the effects of Work Discipline, Work Environment, and Work Motivation on Employee Performance at PT Hillwood. A quantitative approach was adopted, with a sample size of 65 respondents. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS). The findings indicated that while Work Discipline has a significant influence on employee performance, it exhibits a negative relationship. In contrast, both Work Environment and Work Motivation were found to have a positive and statistically significant impact on employee performance at PT Hillwood.